2010
DOI: 10.1038/ijo.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Fat oxidation at rest predicts peak fat oxidation during exercise and metabolic phenotype in overweight men

Abstract: Objective: To elucidate if fat oxidation at rest predicts peak fat oxidation during exercise and/or metabolic phenotype in moderately overweight, sedentary men. Design: Cross-sectional study. Subjects: We measured respiratory exchange ratio (RER) at rest in 44 moderately overweight, normotensive and normoglycemic men and selected 8 subjects with a low RER (L-RER, body mass index (BMI): 27.9±0.9 kg m À2 , RER: 0.76±0.02) and 8 with a high RER (H-RER; BMI 28.1 ± 1.1 kg m À2 , RER: 0.89 ± 0.02). After an overnigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 44 publications
(49 reference statements)
9
64
0
3
Order By: Relevance
“…Contrary to suggestions that a negative energy balance would increase FAT-OX (47), but consistent with the results of Rosenkilde et al (48), we showed no relation between energy balance and the MFO. The potential limitations of the estimation of EI and EI expenditure with the use of a self-report in free-living individuals have been well documented (49, 50).…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to suggestions that a negative energy balance would increase FAT-OX (47), but consistent with the results of Rosenkilde et al (48), we showed no relation between energy balance and the MFO. The potential limitations of the estimation of EI and EI expenditure with the use of a self-report in free-living individuals have been well documented (49, 50).…”
Section: Discussionsupporting
confidence: 89%
“…Workload was increased with 25-W increments every minute after warm-up until exhaustion, and attainment of V O2 max was accepted using previously defined criteria (46).…”
Section: Methodsmentioning
confidence: 99%
“…This trait was already present at young age and may explain reduced blood lipids and the leaner phenotype and better fat tolerance exhibited by Rb ϩ/Ϫ mice later in life. In humans, a low RER predicts a healthy metabolic phenotype in overweight, sedentary men (38), and a high RER (low fat oxidation) has been implicated as a risk factor for weight gain and obesity (3). Animal studies have specifically Fig .…”
Section: E179mentioning
confidence: 99%